Eksplorasi Kepuasan Hidup Laki-Laki Gay Indonesia Dengan Human Immunodeficiency Virus (HIV) - Yaqin, Muhammad Dicky Ainul; Pertiwi, Pradytia Putri (ANIMA Indonesian Psychological Journal, 2025)
Indonesian gay men living with human immunodeficiency virus (HIV) suffer from the effects of the human immunodeficiency virus (HIV) in the physical and psychological aspects of their lives, while also being burdened by the stigma from society related to their sexual orientation and status as people living with HIV (PLHIV). Unfortunately, this topic is inadequately explored in Indonesian academic literature. This study addresses this gap utilizing concurrent-embedded mixed method design by combining quantitative assessments (Satisfaction With Life Scale [SWLS]) with qualitative data from three open-ended questions. The instrument was administered online by adopting a snowball sampling technique to recruit study participants, being: (1) Indonesian men; (2) aged 18 and older; (3) self-identifying as gay men; and (4) living with human immunodeficiency virus (HIV). Analysis of data from 84 study participants from 16 provinces found that 60.7% of the study participants have their life satisfaction score in the Slightly Satisfied to Very Satisfied categories. Self-acceptance, gratitude, and pressure emerged as dialectical aspects of their perceived life satisfaction, with safety and social support identified as primary concerns. These findings highlight the need for further study and research into the life satisfaction of other minority groups, especially Indonesian gay men living with human immunodeficiency virus (HIV). Communities, experts, and policymakers are encouraged to raise awareness about human immunodeficiency virus (HIV)-related issues to foster safety and social support. Ensuring the availability of equitable mental health services and access to employment and entrepreneurship is also a critical concern.